2020
DOI: 10.3389/fmicb.2020.01593
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Methods for the in vitro Susceptibility Testing of Dermatophytes

Abstract: Objectives: Infections caused by dermatophytes affect a high percentage of the population. Antifungal susceptibility testing (AST) can offer useful information about the susceptibility profiles of the pathogens as well as the concomitant documentation of the appropriate treatment. However, the slow growth rate of these fungi and their poor sporulation are factors that can delay and affect the performance of the AST. The proposed methods by the CLSI or the EUCAST are both laborious for the everyday routine. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…However, no such standards are available for dermatophytoses. As most of the recent worldwide susceptibility data of ITZ vis a vis dermatophytes suggests that this class of fungi are largely sensitive to ITZ, 1,2,7,19 it is probable that levels achieved in the serum and as a corollary in the stratum corneum are predictive of treatment outcomes. Thus, it is plausible that clinical failures with ITZ may represent inadequate serum levels, and thus, there is a need to study cut-off serum levels which can predict optimum dosing, and lead to better and more predictable treatment outcomes with ITZ in tinea corporis/cruris.…”
mentioning
confidence: 99%
“…However, no such standards are available for dermatophytoses. As most of the recent worldwide susceptibility data of ITZ vis a vis dermatophytes suggests that this class of fungi are largely sensitive to ITZ, 1,2,7,19 it is probable that levels achieved in the serum and as a corollary in the stratum corneum are predictive of treatment outcomes. Thus, it is plausible that clinical failures with ITZ may represent inadequate serum levels, and thus, there is a need to study cut-off serum levels which can predict optimum dosing, and lead to better and more predictable treatment outcomes with ITZ in tinea corporis/cruris.…”
mentioning
confidence: 99%
“…A change in colour from blue (oxidised state) to pink (reduced) indicated fungal growth. Some studies have evidenced that use of Alamar Blue does not affect the MIC values, but makes it more evident to read for dermatophyte 31 . Discrepancies in the MICs or MECs between the two methods indicated that the concentration of Alamar Blue should be explored for each antifungal agent and each different species of dermatophyte.…”
Section: Discussionmentioning
confidence: 99%
“…Add 50 µL test microorganism inocula; and 30 µL resazurin at 0.015 mg/mL as an indicator for cell viability; plates were incubated at 35 o C for 16-48 hours [29]. The MIC endpoints were observed visually when viable cells changed their colour from purple to pink [30].…”
Section: Microdilution Methodsmentioning
confidence: 99%